Atypical Kawasaki disease in a 13-year-old boy. - Agarwal, S.; Sharma, R.; Sharma, P.; Saini, Y.; Awasthi, S.; Nijhawan, M. (European Journal of Pediatric Dermatology, 2023)
Kawasaki disease is a systemic disorder manifesting as vasculitis of medium-sized and small vessels. The diagnosis of Kawasaki disease is based on clinical criteria and should be suspected even when the clinical features are not complete. Any child suspected of having Kawasaki disease should be investigated comprehensively because prompt diagnosis and early administration of intravenous immunoglobulins and aspirin significantly reduce the risk of coronary complications. In the present report we described a rare case of atypical Kawasaki disease in a 13-year-old boy with prolonged fever, skin exfoliation, non-purulent conjunctivitis, inflamed strawberry tongue, cervical and inguinal lymphadenopathy, and arthralgia. The patient was thoroughly investigated and was treated with intravenous immunoglobulins and aspirin as per protocol.